2014
DOI: 10.5365/wpsar.2014.5.3.002
|View full text |Cite
|
Sign up to set email alerts
|

A marked decline in the incidence of malaria in a remote region of Malaita, Solomon Islands, 2008 to 2013

Abstract: The decline in malaria cases in the AAH catchment area has been spectacular, particularly for Pf. This was supported by three sources of hospital surveillance data (laboratory, admissions and treatment records). The decline was associated with the use of artemisinin-based combined therapy and improved vertical social capital between the AAH and the local communities. Calculating village-specific API has highlighted which villages need to be targeted by the AAH malaria control team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…However, it has been previously recognized that the accuracy of clinical malaria case reporting in primary health care facilities in Solomon Islands is often relatively poor [42]. In addition, the results of this study are well in line with the changes observed at a remote region of Malaita, the neighbouring island to Ngella, where in parallel with a 91% reduction in all malaria cases, the proportion of clinical cases due to P. vivax increased from 33% in 2008 to 84% in 2013 [43]. While further studies will be required to determine the relative contribution of P. falciparum and P. vivax to the burden of clinical malaria in Ngella, data of this study make it clear that the very high burden of asymptomatic, low-density P. vivax infections is the key challenge to future malaria elimination in Ngella.…”
Section: Discussionsupporting
confidence: 86%
“…However, it has been previously recognized that the accuracy of clinical malaria case reporting in primary health care facilities in Solomon Islands is often relatively poor [42]. In addition, the results of this study are well in line with the changes observed at a remote region of Malaita, the neighbouring island to Ngella, where in parallel with a 91% reduction in all malaria cases, the proportion of clinical cases due to P. vivax increased from 33% in 2008 to 84% in 2013 [43]. While further studies will be required to determine the relative contribution of P. falciparum and P. vivax to the burden of clinical malaria in Ngella, data of this study make it clear that the very high burden of asymptomatic, low-density P. vivax infections is the key challenge to future malaria elimination in Ngella.…”
Section: Discussionsupporting
confidence: 86%
“…2 In 2014 the rate of confirmed cases of malaria was 44 per 1000 person years. 3 Malaria has been reported to have declined as a cause of fever in some parts of the Solomon Islands in the last ten years 4 but remains an important public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of malaria that causes fever has been declining in some parts of Solomon Islands from 2008 to 2013. ( 9 ) Studies in nearby countries including West Papua, Indonesia have shown rickettsia infections are a common cause of acute infections that lead to hospitalization. ( 10 ) Results of our study may give some insights for the incidence of rickettsia infections in Solomon Islands; however, in the absence of routine testing, the proportion of rickettsial infections that causes febrile illnesses in Solomon Islands is still unclear.…”
Section: Discussionmentioning
confidence: 99%